Serving to Strengthen: How Coaching Enhances the Impact of Servant Leadership on Teacher Competence - Yulianto, Septian; Ricky, Ricky; Setiawan, Roy (Universitas Kristen Petra, 2026)
As a newly established school implementing a curriculum that differs from other schools under the same foundation, a newly established private Christian senior high school in Sidoarjo faces the challenge of improving educational quality through teacher competency development. This study examines the effect of servant leadership on teacher competency, with coaching as a moderating variable. Using a quantitative approach, the study employed Partial Least Squares Structural Equation Modeling (PLS-SEM). Data on servant leadership and coaching were collected through questionnaires distributed to 38 teachers, while teacher competency data were obtained from secondary data provided by school leaders. The findings show that servant leadership has a positive and significant effect on teacher competency. Coaching does not have a significant direct effect on teacher competency; however, it strengthens the positive relationship between servant leadership and teacher competency. These findings suggest that servant leadership, when supported by structured coaching practices, can contribute more effectively to teacher development and educational quality improvement.